2019
DOI: 10.1021/acs.orglett.9b03100
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Two Cytochrome P450s in Tiacumicin Biosynthesis Reveals Reaction Timing for Tailoring Modifications

Abstract: Functions of the tailoring enzymes for the biosynthesis of tiacumicin B (1) have been previously determined. However, the reaction timing remains elusive. Herein, we report the in vitro biochemical characterization of two P450 enzymes TiaP1 and TiaP2. The investigation of their substrate scope and kinetic parameters clearly demonstrates that the TiaP2-catalyzed C-20 hydroxylation is the first tailoring step and the TiaP1-catalyzed C-18 hydroxylation is the last step in the biosynthesis of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…hamdenensis , one of the known producer strains . According to sequence analysis and analysis of truncated products isolated from the fermentation broth of gene‐knockout mutants a possible biosynthetic pathway was proposed …”
Section: Investigation Of the Biosynthetic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…hamdenensis , one of the known producer strains . According to sequence analysis and analysis of truncated products isolated from the fermentation broth of gene‐knockout mutants a possible biosynthetic pathway was proposed …”
Section: Investigation Of the Biosynthetic Pathwaymentioning
confidence: 99%
“…The complete catalytic order of the assembly of the final natural product 1 remains elusive. However, latest investigations indicated that TiaP2 first oxidizes macrocycle 32 at the C(20)‐position, before glycosyltransferase TiaG1 attaches the noviose to form alcohol 42 . Then, the isobutyric ester is attached by acyltransferase TiaS6 or rhamnosylation occurs to construct fidaxomicin scaffold 43 .…”
Section: Investigation Of the Biosynthetic Pathwaymentioning
confidence: 99%
“…18,22,23 So far, most known derivatives were obtained through fermentation of gene-knockout mutants of the producer strain. [24][25][26][27] Furthermore, several compounds with a similar scaffold were found along with fidaxomicin (1), some of which lack the rhamnoseorsellinate moiety and/or the noviose. 8,28 Those truncated products missing one of the sugar moieties display significantly decreased antibiotic activity and thereby point out the importance of these carbohydrate units.…”
Section: Introductionmentioning
confidence: 99%
“…Although fidaxomicin has a high potential to deliver next-generation antibiotics, there are only few successful approaches toward new derivatives documented that might broaden structure-activity relationship (SAR) information and thereby further extend its application 18,28,29 . So far, most known derivatives were obtained through fermentation of geneknockout mutants of the producer strain or by chemical modification of the homoorsellinic acid moiety [30][31][32][33][34][35] . Furthermore, several compounds with a similar scaffold were found along with fidaxomicin (1), some of which lack the rhamnose-orsellinate and/or the noviose moiety 8,36 .…”
mentioning
confidence: 99%